解方程(-4x-5)2=(-2x+3)(-2x-3)-2(2x+3)(-3x+5)
1个回答
16x²+40x+25=4x²-9+12x²-2x-30
40x+25=-2x-39
42x=-64
x=-32/21
相关问题
解方程:4x/(x^2+x+3)+5x/(x^2-5x+3)=-3/2
解方程(1)3x-2=-5 (2)-5x+2=3x-4 (3)2x-3(10-x)=5 (4)3(x-1)=3-(2x+
5/x+4-(x-5)=3/x+3-2/x-2 解方程
解方程3X-1/X+2=2/3 解方程:X-6/X-3 + X-4/X-5=2 解方程:2/X+1 + 3/X-1 =
解方程(2x+4)/5-(x-1)=(2x+3)/3-(3x-2)/2
解方程:2(x-3)(x+5)=x²+ (x-2)(x+2)和(-4x-5)²=(-2x+3)(-2
解方程【-4x-5】的两次=【-2x+3】【-2x-3】-2【2x+3】【-3x+5]
解方程2X(X-3)-x(4-3X)=5X²-3X+2
解方程2x(x-3)-(4-3x)x=5x²-3x+2
解方程:(1)5x=3x+4(2) 3x+5 2 =3- 7-3x 5 .